2007
DOI: 10.1177/1086026607305740
|View full text |Cite
|
Sign up to set email alerts
|

School Custodians and Green Cleaners

Abstract: Coalitions between labor unions and environmental organizations often dissolve in class tensions that appear to force unions to choose between job security and occupational or environmental health. This article examines a successful blue-green coalition that worked to substitute cleaning products used in Boston public schools with safer alternatives. The coalition succeeded in part through the role of bridge builders, who unified a diverse group of stakeholders, including community and environmental health adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Custodians noted the importance of a strong feedback mechanism among end users (custodians), purchasers, and other stakeholders within the institutional community. This was consistent with another green cleaning study reporting worker perceptions of not being part of the selection process and concerns about equipment and training [34]. Quinn (2006) explains that the successful introduction of an alternative involves a social process in addition to a technical one, and that interventions are more successful when all parties impacted feel they were represented in the change.…”
Section: Summary and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Custodians noted the importance of a strong feedback mechanism among end users (custodians), purchasers, and other stakeholders within the institutional community. This was consistent with another green cleaning study reporting worker perceptions of not being part of the selection process and concerns about equipment and training [34]. Quinn (2006) explains that the successful introduction of an alternative involves a social process in addition to a technical one, and that interventions are more successful when all parties impacted feel they were represented in the change.…”
Section: Summary and Discussionsupporting
confidence: 80%
“…Senier found that personal experience mediates acceptance: "if custodians were confused or unclear about the importance of health in making the shift to green, it may have reduced their subjective assessment of the new EPP, as their application often significantly differs from traditional products and requires more physical labor" [34]; this may have been true for our study.…”
Section: Limitations Of the Studymentioning
confidence: 77%
“…Our results provide insight on organizational interactive strategies that affect the success of environmental initiatives (Shwom, 2009;Vasi, 2006). In this case, we saw that leadership was able to motivate pro-environmental behavior from people with a variety of values-even from staunch anti-environmentalists-which adds to previous research on environmental initiatives that successfully negotiate political divides (Daub, 2010;Senier, Mayer, Brown, & Morello-Frosch, 2007). In the past decade, for instance, as green building benefits and climate change effects have become more scientifically evident, public belief in anthropogenic climate change has declined (Dunlap & McCright, 2008), and scholars question as to whether this debate has become too divisive for collaboration (Hoffman, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…For the firefighting community, this is obviously a trade-off that is carefully considered: when it comes to personal and professional safety, anything that decreases fire safety is seen as harmful. This is similar to another blue-green coalition between environmentalists and janitors, in that janitors do not want to sacrifice product efficacy for product safety [54].…”
Section: Safer Alternativesmentioning
confidence: 79%
“…A New Jersey coalition supported the movement of a right-to-know bill through the state legislature [51]. In Boston, occupational health activists, school janitors, and teachers collaborated to test environmentally safe cleaning products in public schools [54]. Moving forward, the "green economy" focused on renewable energy and sustainability is seen as a promising avenue for blue-green coalitions [55], and this area has been identified as an emerging area of social science inquiry [56].…”
Section: The Flame Retardant Advocacy Coalitionmentioning
confidence: 99%